Leukotriene B4 receptor 2 regulates the proliferation, migration, and barrier integrity of bronchial epithelial cells. Issue 8 (7th March 2018) - Liu, Min; Shen, Juan; Yuan, Huimin; Chen, Fengling; Song, Huaidong; Qin, Hui; Li, Yanqin; Xu, Jiabo; Ye, Qing; Li, Shenxian; Saeki, Kazuko; Yokomizo, Takehiko
Abstract : The airway epithelium plays a crucial role in the pathogenesis of asthma. The functions of leukotriene B4 receptor 2 (BLT2) on the airway epithelial cells remains unknown. In our study, BLT2 expression in 16HBE bronchial epithelial cells were manipulated by transfection with BLT2 overexpression plasmid or BLT2 small interference RNA. 16HBE cells were then exposed to BLT2 antagonist (LY255283) or BLT2 agonist (12(S)‐hydroxyheptadeca‐5Z, 8E, 10E‐trienoic acid [12‐HHT] or CAY10583). The results showed that BLT2 overexpression, 12‐HHT stimulation, or CAY10583 treatment resulted in the enhanced proliferation and migration of 16HBE cells. In addition, BLT2 showed an inhibitory effect on epithelial permeability as illustrated by the measurement of transepithelial electrical resistance (TER) and epithelial permeability, and a promoting effect on the levels of tight junction proteins (occludin and claudin‐4) and phosphorylated p38 as demonstrated by real‐time PCR and Western blotting analyses. These results suggest BLT2 as a key determinant of airway epithelial barrier integrity. On the contrary, RNAi‐mediated knockdown or LY255283 treatment had reversed effects on the proliferation, migration, and epithelial barrier integrity. Together, our findings suggest the critical roles of BLT2 on the functions of bronchial epithelial cells and that BLT2 agonists are potential therapeutic agents for asthma treatment. Abstract : BLT2 regulated the proliferation and migration of 16HBE cells. BLT2 was a key determinant of airway epithelial barrier integrity.